Susceptibility Weighted Imaging as a Useful Imaging Adjunct in Hemichorea Hyperglycaemia. (23rd May 2013) - Dharsono, Ferry; Thompson, Andrew; van Heerden, Jolandi; Cheung, Andrew
Abstract : Hyperglycaemia with hemichorea (HGHC) is an unusual clinical entity that can be associated with corpus striatum hyperintensity on T1-weighted (T1W) magnetic resonance imaging (MRI) sequences. We report the utility of the susceptibility weighted image (SWI) sequence and the filtered phase SWI sequence in the imaging assessment of HGHC.